2013
DOI: 10.1353/pla.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Library Use and Undergraduate Student Outcomes: New Evidence for Students’ Retention and Academic Success

Abstract: Academic libraries, like other university departments, are being asked to demonstrate their value to the institution. This study discusses the impact library usage has on the retention and academic success of first-time, first-year undergraduate students at a large, public research university. Usage statistics were gathered at the University of Minnesota during the Fall 2011 semester for thirteen library access points. Analysis of the data suggests first-time, first-year undergraduate students who use the libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
142
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 16 publications
7
142
1
Order By: Relevance
“…The observable trend for GPA in the data supports the results found by Soria et al (2013), indicating that GPA has a small effect on engagement with the library. As students' cumulative GPA rose, so too did the students' willingness to interact with the online instructional module.…”
Section: Discussion/future Directionssupporting
confidence: 84%
See 1 more Smart Citation
“…The observable trend for GPA in the data supports the results found by Soria et al (2013), indicating that GPA has a small effect on engagement with the library. As students' cumulative GPA rose, so too did the students' willingness to interact with the online instructional module.…”
Section: Discussion/future Directionssupporting
confidence: 84%
“…The study was narrowly focused on engagement with online instruction itself, to see if the broader claims about library engagement in general, made by Soria et al (2013), apply to the specific context of library pedagogy. In response to fairly extensive research on engagement in online learning by different demographic groups in higher education, the authors chose to continue that line of research into online library instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conway (2015) and Howard, Nicholas, Hayes, and Appelt (2014) likewise found that students were more likely to use library resources after library instruction, but also found that the one-shot instruction did not increase either the quantity or diversity of sources cited. Soria, Fransen, and Nackerud (2013) found significant impacts on student GPA and retention for a number of library-related interactions, including database use, use of electronic journals, and use of computer workstations, but did not find a significant relationship between GPA or retention and library instruction. Academic librarians have given a great deal of focus on understanding how to either enhance effectiveness of the one-shot interaction or to address whether the assessment tools used are appropriate measures of the 7 authentic outcomes.…”
Section: Information Literacy and Embedded Librarianshipmentioning
confidence: 70%
“…Results indicate that the probability of using library resources was a function of student characteristics: clearly, some students were more likely to use library resources than other students. Asian students were more likely to use workstations compared to Black students, when workstation usage was defined as (1) having logged in at least once and (2) having logged in at least five times. For example, when workstation usage was defined as having logged in to a workstation at least five times during the term, Asian students were found to be 31 percent more likely to use workstations than Black students.…”
mentioning
confidence: 99%